Evaluation of Lumbar Disc Degenerative Disease on MRI in Disability Index - Ahmed, Laraib; Noman, Ali; Ali, Akhtar; Munir, Ameerab; Javed, Shama; Asghar, Sabiha; Ahmed, Jahanzaib (Indus Journal of Bioscience Research, 2025)
Background: Lumbar disc degeneration (LDD) results from aging, mechanical stress, genetics, and lifestyle factors, causing disc dehydration, height loss, and herniation. MRI helps assess these changes, which often correlate with disability indices like the Oswestry Disability Index (ODI). Understanding this link improves diagnosis and treatment. This study explores the relationship between MRI findings and disability scores for better patient care. Objective: Evaluation of lumber disc degeneration on MRI in disability index. Methodology: This cross-sectional and observational study was conducted over four months with a sample size of 96 participants, selected through convenience sampling. It included patients with radiating or non-radiating limb pain and chronic back pain lasting over three months from October 2024 to January 2025. Patients with congenital spinal abnormalities or MRI contraindications were excluded to ensure imaging accuracy and safety. Results: This study analyzed 96 patients to evaluate the impact of lumbar disc degeneration on the disability index using MRI findings. Right leg pain was reported in 63 (65.6%) patients, while left leg pain was noted in 66 (68.8%) cases. Disc degeneration and stenosis were observed in 43 (44.8%) patients each, while disc bulge was the most prevalent finding in 70 (72.9%) cases. Moderate to severe disability was recorded in 87 (90.6%) patients, highlighting a strong correlation between MRI findings and functional impairment. Conclusions: Increased lumbar IDD in MRI goes along with an increased DI. Thus, MRI is a strong indicator of a patient’s clinical appearance. However, low back pain and left/right leg numbness/pain cannot be explained by imaging alone. Clinical correlation is imperative for an adequate diagnostic advance in patients with low back pain, left/right leg pain/ numbness.